Síntese de 2-alquinil telurofenos via reação de sonogashira entre 2-halotelurofeno e 1-alcinos - Panatieri, Rodrigo Barroso (2006)
We present herein our results of the palladium-catalyzed cross-coupling of 2-halotellurophenes with several terminal alkynes to give acetylenic tellurophene derivatives in excellent yields. Our initial efforts were devoted to the selection of a suitable catalyst system for efficient Sonogashira coupling reaction between 2-halotellurophenes and terminal alkynes. To this end 2-iodo-5-butyl-tellurophenes and propargyl alcohols were treated at room temperature, with Pd(0) and Pd(II) catalysts, in the presence or in the absence of CuI, Et3N and using different solvents. Thus, PdCl2(PPh3)2, CuI , THF and Et3N at room temperature for 12 h was chosen as the optimum condition for this coupling reaction. In order to demonstrate the efficiency of this reaction, we explored the generality of our method extending the conditions to other terminal alkynes and the products were obtained in good yields (54 - 98%). Concerning the structure of tellurophenes, we found that both butyl and phenyl iodotellurophenes were suitable for in this methodology. After the reaction conditions for 2-iodotellurophenes have been optimized, we turned our attention to 2-bromotellurophenes. Thus, extending the standard catalytic system, used to the coupling reaction described for 2-iodotellurophenes, to the reaction of 2-bromotellurophenes with terminal alkynes it was possible to obtain the desired products in lower yields (38 - 66%). Toxicological and pharmacological activities of these compounds are under study in our laboratory. Compounds A and B at 300 mM reduced lipid peroxidation about 30% and did not present thiol-oxidase activity. d-Aminolevulinate dehydratase (d-ALA-D) activity, an enzyme sensible to organochacogen compounds, was inhibited by 300 mM of compound B (about 35%), conversely compound A did not change the enzyme activity. Additionally, previous studies of the reaction conditions between 2- butyltelluro-tellurophenes and terminal alkynes resulted in the corresponding cross coupled product in moderate yield (66%), indicating the viability of these compounds as substrates in Sonogashira reactions.